The Inheritance of the Precept Tradition in 18th- and 19th-Century East Asian Buddhism and the Prelude to Modernity: Comparing the Korean and Japanese Precept Revival Movements - Jarang Lee (Religions)
This article compares the precept revival movements in Korean and Japanese Buddhism in the early modern period. It examines how monks in both countries, in particular, in the Korean Hyujŏng lineage and the Japanese Shingon sect, restored and utilized the precept tradition to re-establish Buddhist identity in the midst of rapid political and social change. Although in different ways, Buddhism in the early modern period in both countries experienced state control and an anti-Buddhist milieu, making it difficult to maintain its religious identity. Various efforts were made to overcome this hardship, the most prominent of which was the precept revival movement. In the early 19th century, in Chosŏn Korea, Taeŭn and Paekp’a sought to restore the bhikṣu lineage by overhauling the bhikṣu ordination rituals through the “reception of the precepts through an auspicious sign” and “the reception of the ten wholesome precepts”, respectively, while in mid-to-late 18th-century Japan, the Shingon master Jiun advocated a return to the teachings of Śākyamuni through the Shōbō-ritsu movement. While both countries focused on precept revival as a way to solidify Buddhist religious identity, Korea emphasized the restoration of the bhikṣu lineage, while Japan, especially in the Shingon-shū, emphasized a return to the fundamental teachings of the Buddha. These differences stem from the unique historical backgrounds of the two countries and the distinctive developments of their Buddhist traditions. By comparing the precept revival movements in both countries, this study examines how different precept traditions influenced the identity of East Asian Buddhism in the early modern period and how these efforts have been fundamental in maintaining Buddhist orthodoxy into the modern era.